2014
DOI: 10.11604/pamj.2014.19.330.5542
|View full text |Cite
|
Sign up to set email alerts
|

Hydatid cyst of the pericardium: a case report

Abstract: Pericardial hydatid cystis a rare condition; its clinical presentation is variable. It can reveal straightaway at the stage of life threatening complications. We report the case of a 17 years old female Arab patient, who complained of a sudden onset dyspnea, clinical examination was poor; the diagnosis was suspected by echocardiography and confirmed by the CT scan and hydatid serology. Furthermore, no other location was noted. Surgical treatmentwas proposed. The modern cross-sectional imaging especially CT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Clinical features depend on the size and location of the cysts and involvement of neighboring structures [ 2 , 6 ]. Patients are usually asymptomatic, or may present with mild, recurrent, non-specific chest pain, owing to pericarditis resulting from episodes of partial rupture into the pericardium, or external compression over the coronary artery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical features depend on the size and location of the cysts and involvement of neighboring structures [ 2 , 6 ]. Patients are usually asymptomatic, or may present with mild, recurrent, non-specific chest pain, owing to pericarditis resulting from episodes of partial rupture into the pericardium, or external compression over the coronary artery [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis is established on the basis of ultrasound examination, CT scan and serology [ 8 ]. Cardiac magnetic resonance imaging (MRI) can provide interesting information in case of discrepancy between echocardiography and CT scan [ 6 ]. Serological studies are not found to be sensitive for the diagnosis, however in our case, hydatid serology was positive [ 9 ].…”
Section: Discussionmentioning
confidence: 99%